Psycho-behavioural impact of ‘Lockdown’ due to COVID-19 pandemic in Nepal: An Online Survey - Gupta, AK; Mehra, A; Sahoo, S.; Pokhrel, P; Grover, S (Journal of Psychiatrists’ Association of Nepal, 2020)
Introduction: Nepal entered into a lockdown mode since 24th March 2020 to control the spread of COVID-19 infection. Our aim was to evaluate the mental and behavioural impact of lockdown due to COVID-19 pandemic on the general public of Nepal in terms of the point prevalence of sadness, anxiety, feelings and relationship issues due to lockdown. Material And Method: It was a web-based cross-sectional survey conducted by using the Survey Monkey platform during 8th April 2020 and 29th April 2020. The link generated was circulated on Whatsapp platforms. Self-designed clinical profile was made to assess different feelings, leisure activities and relationship changes with family members that are not assessed using scale. The survey link was circulated starting from 8th April 2020 and was closed on 29th April 2020. Results: Of the 142 participants about 35.9% reported being sad, 28.2% had anxiety and about 46.5% of the participants felt lonely. Fear of death (60.6%) and getting infected with corona (52.1%) were the most common stress. Most of them were involved in sexual activities (67.6%) and reading books (42.3%) during lockdown. Some (14.8% and 18.3%) reported marked improvement in relationships with parents and children respectively. Conclusion: The present survey suggests that substantial proportion of the population do not report change in relationship despite reporting sadness, loneliness and change in daily activities. Therefore, social relationship and brotherhood need to be advised in addition to minimising emotional distancing during awareness programs related to COVID-19.